Frequency of Complications of Ileostomy in the Management of Ileal Perforation Secondary to Typhoid Fever (Medical Forum Monthly, 2022)
Objective: To determine the frequency of complications of ileostomy in the management of ileal perforation secondary to typhoid fever in a tertiary setting.Study Design: Descriptive StudyPlace and Duration of Study: This study was conducted at the Department of Surgery, Bolan Medical College, Quetta from February 2020 to February 2021 for a period of one-year.Materials and Methods: Ninety patients with single or multiple ileal perforation due to typhoid fever confirmed by clinical features, laboratory tests and abdominal x-ray were included in this study. Patients were observed for complications of ileostomy like skin excoriation, stoma retraction, stenosis, prolapse, peristomal sepsis, parastomal hernia, necrosis and death for two months.Results: The average age of the patients was 40.30±10.14 years. Skin excoriation was the commonest complication that was observed in 18.9% cases followed by stoma retraction 10%, parastomal hernia 10%, stenosis 4.4%, prolapse 3.3%, peristomal sepsis 6.7% and necrosis 2.2%. Mortality was observed in 6.67% (6/90) due to stoma.Conclusion: In this study skin excoriation was the commonest complication. Early surgery and adequate resuscitation are the important factors for successful management of patients with ileal perforation. Primary closure of perforation is a preferred technique in clinically stable patients with a single perforation with minimal soiling of the abdominal cavity, to avoid complications related to stoma.